تاثير الثقافة التنظيمية على الاداء الوظيفي للعاملين - شاكر بالهادي; عبد الله بن سعد (جامعة الوادي - University of Eloued, 2025)
"تهدف الدراسة الحالية إلى التعرف على تأثير الثقافة التنظيمية على الاداء الوظيفي، حيث كانت الإشكالية كما يلي: - كيف يؤثر تباين الثقافة التنظيمية بين المؤسسات على الأداء الوظيفي للعاملين؟. ومن خلال هذا التساؤل وضعنا مجموعة من الأهداف في شكل فرضيات وهي: - تطابق الثقافة التنظيمية للمؤسسة مع ثقافة العامل يرتبط بأداء العاملين، حيث يمكن أن يكون الانسجام بين قيم المؤسسة وقيم العامل الموظف لها دورا مهما في تعزيز أدائه الوظيفي. - تأثير الثقافة التنظيمية على مستوى الابتكار والإبداع للعاملين إذ يفترض أن بعض الثقافات التنظيمية قد تشجع على الابتكار والتجديد بينما قد تكون أخرى محافظة. - التأثير المتبادل بين القيادة والثقافة التنظيمية على الأداء الوظيفي، إذ يمكن أن تؤثر أساليب القيادة وتفاعلها مع الثقافة التنظيمية على مستوى أداء العاملين. وبعدها تم التطرق للجانب النظري للدراسة من خلال تناول متغيري الدراسة بالتعريف،ثم قمنا بإجراء الدراسة الميدانية انطلاقا من الفرضية العامة والفرضيات الجزئية، وذلك للتعرف على درجة هذه الأخيرة فاعتمدنا للتأكد من صحة الفرضيات على استمارة بيانات عن تأثير الثقافة التنظيمية على الأداء الوظيفي. ""The curent study aims to identify the impact of organizational culture on job performance. The problème was as follows: - How does the variation in organizational culture between institutions affect employee job performance? Based on this question, we formulated a set of objectives in the form of hypotheses: - The congruence of an organization's organizational culture with that of its employees is linked to employee performance, as harmony between the organization's values and those of its employees can play an important role in enhancing job performance. - The impact of organizational culture on employee innovation and creativity, as it is assumed that some organizational cultures may encourage innovation and renewal, while others may be conservative. - The reciprocal influence between leadership and organizational culture on job performance, as leadership styles and their interaction with organizational culture can affect employee performance The theoretical aspect of the study was then addressed by defining the study variables. We then conducted a field study based on the general hypothesis and the partial hypotheses to determine the degree of the latter. To verify the validity of the hypotheses, we relied on a data form on the impact of organizational culture on job performance. "
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع تنظيم وعمل.
Keywords: الحوافز; القيم التنظيمية; الاداء الوظيفي; الثقافة التنظيمية; Organizational culture; job performance; organizational values; incentives